The soul of Spain [videorecording] - Birch, Miriam; National Geographic Society (Washington, D.C.).; WQED (Television station : Pittsburg, Pa.). (Washington, D.C. The Society, 1991)
Examines the remarkable transformation of the economic, political and social structure that continuously take place in Spain.
VHS.
Credits : Edited by Oska Dektyar.
Keywords: National characteristics, Spanish; Spain -- Social life and customs; Spain -- Description and travel